An extreme climatic event alters marine ecosystem structure in a global biodiversity hotspot - Wernberg, T.; Smale, D.; Tuya, F.; Thomsen, M.; Langlois, T.; De Bettignies, T.; Bennett, Scott; Rousseaux, C. (2013)
Extreme climatic events, such as heat waves, are predicted to increase in frequency and magnitude as a consequence of global warming but their ecological effects are poorly understood, particularly in marine ecosystems. In early 2011, the marine ecosystems along the west coast of Australia - a global hotspot of biodiversity and endemism - experienced the highest-magnitude warming event on record. Sea temperatures soared to unprecedented levels and warming anomalies of 2-4C persisted for more than ten weeks along >2,000 km of coastline. We show that biodiversity patterns of temperate seaweeds, sessile invertebrates and demersal fish were significantly different after the warming event, which led to a reduction in the abundance of habitat-forming seaweeds and a subsequent shift in community structure towards a depauperate state and a tropicalization of fish communities. We conclude that extreme climatic events are key drivers of biodiversity patterns and that the frequency and intensity of such episodes have major implications for predictive models of species distribution and ecosystem structure, which are largely based on gradual warming trends. © 2013 Macmillan Publishers Limited. All rights reserved.